46. CLINICAL AND PARACLINICAL CHARACTERISTICS OF IMPACTED MANDIBLE WISDOM TEETH ACCORDING TO PARANT II AT CLINICAL CENTER OF DENTISTRY, HONG BANG INTERNATIONAL UNIVERSITY (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical characteristics of impacted mandibular third molars classified as Parant II at the Clinical Center of Odonto-Stomatology, Hong Bang International University.Materials and methods: A cross-sectional descriptive study was conducted on 91 impacted mandibular third molars indicated for surgical removal under the Parant II classification. Data on demographics, clinical features (tooth position, impaction status, gingival condition), and radiographic features (Pell-Gregory classification, angulation, root morphology, relationship to the inferior alveolar canal) were collected and analyzed using descriptive statistics.Results: The mean age of the subjects was 24.3 ± 3.8 years, with the 18-24 age group being the most predominant. The gender distribution was nearly equal (51.9% male, 48.1% female). Radiographically, Pell-Gregory class II (87.91%) and position A (62.64%) were the most common findings. Mesioangular impaction was the most prevalent angulation (40.66%), followed by horizontal (25.27%). Straight root morphology was predominant (67.03%). A close relationship or contact with the inferior alveolar canal was observed in 53.85% of cases. Most teeth (97.8%) showed no clinical signs of gingival inflammation.Conclusion: Parant II impacted mandibular third molars at the study site were primarily found in young adults, with no significant gender difference. The common morphological patterns included mesioangular impaction, a shallow position (class II, position A), straight roots, and a high prevalence of proximity to the inferior alveolar canal. These findings are consistent with other Vietnamese studies and provide crucial data for preoperative assessment and surgical planning.
Keywords: Mandibular third molar; impacted tooth; Parant II classification; clinical characteristics; radiographic features.